The adequacy of ANC components received and associated factors among women of reproductive age in Tanzania. - Jovin R Tibenderana; Sanun Ally Kessy; Dosanto Felix Mlaponi; John Elyas Mtenga; Jomo Gimonge; Ndinagwe Lloyd Mwaitete; Fabiola V Moshi (PLoS ONE)
Background ANC continues to be a vital and crucial component of care for expectant mothers and their unborn children, not only by lowering maternal mortality but also perinatal deaths and connecting them to postnatal treatment. There are limited information about the adequate Antenatal Care (ANC) components coverage, therefore this study aimed at examining the proportion of ANC components coverage, distribution pattern and its associated factors obtained by women of reproductive age (WRA) in Tanzania. Methods This was analytical cross-sectional study among women of reproductive age in Tanzania, utilizing data from the Demographic and Health Surveys (DHS) 2022. Analysis considered the complex survey design through application of weights, clustering and strata. Modified Poisson regression models estimated the factors associated with adequate reception of ANC components among WRA in Tanzania. All analyses were performed in STATA software version 18. Results The proportion of WRA who had received adequate ANC component coverage was 41%. Distribution of ANC contents ranged from 0.5% to 41% for none to seven components respectively. Almost all women (96.1%) had their baby's heartbeat checked. Various factors such as education, wealth index, age, residence, number of ANC visits and birth order were significantly associated with uptake of ANC components among WRA in Tanzania. Conclusion The overall findings suggest a notable disparity in the utilization of ANC services, as fewer than half of women of reproductive age (WRA) are receiving sufficient ANC coverage. Therefore, integrated approaches involving health care facilities and communities, innovative strategies targeting young adults, and strengthening the policy of four or more ANC visits with regular monitoring and data collection are recommended to improve ANC access, utilization, and alignment with WHO guidelines.